ABO blood groups and liver cancer: prospective results from an HBsAg cohort study - Jian Zhu; Jun Xu; Ling-Ling Lu; Yong-Hui Zhang; Mei-Hua Yao; Jian-Hua Lu; Yong-Sheng Chen; Hai-Zhen Chen; Jian-Guo Chen (BMJ Open, 2021)
Objective The association between ABO blood group and risk of liver cancer is unclear, although few studies have reported positive results. This study examined the relationship between ABO blood group and liver cancer in hepatitis B surface antigen (HBsAg)-positive individuals.Design A high-risk population-based cohort study.Setting The study was started in 2007 and closed in 2019; the number of observed person-years as obtained by ABO blood group.Participants The study included 3663 individuals with positive HBsAg, including men aged 30–70 and women aged 40–70.Outcome measures The frequencies of ABO group in the cohort population and patients with liver cancer were calculated, respectively. χ2 test was used to compare differences, and the relative risk (95% CI) for development of liver cancer was evaluated.Results The frequency distribution of blood types A, B, O and AB was 1118 (30.52%), 1073 (29.29%), 1104 (30.14%) and 368 (10.05%), respectively, among 3663 cohort individuals. In the cohort, patients with liver cancer (n=336) were of the following frequencies: type A: 104 (30.95%); type B: 97 (28.87%); type O: 95 (28.27%); and type AB: 40 (11.90%). No significant difference was found between patients with liver cancer and other individuals. The annual incidence rate of liver cancer was 906.34 per 100 000 person-years, and for blood type A, B, O and AB the rates were 917.76, 893.78, 846.02 and 1093.43 per 100 000 person-years, respectively. The relative risk (95% CI) was 0.97 (0.74 to 1.29), 0.92 (0.70 to 1.22) and 1.19 (0.82 to 1.72) for blood types B, O and AB, respectively, compared with blood type A.Conclusion There were no significant differences in the frequency distribution of ABO blood groups in patients with liver cancer within this high-risk cohort, which demonstrates lack of positive association between ABO blood group and risk of liver cancer.